829 Is There an Ongoing Role For 'Telephone Triage Clinics' Post COVID-19?. (4th May 2021) - Holmes, B; Mirza, U; Manning, C; Cooke, R; Jugdey, R
Abstract: Introduction: COVID-19 has placed unprecedented demand on services at ELHT and it has become necessary to have telephone clinics to reduce the number of face-to-face clinics. A 'telephone triage clinic' was set up for referrals from A&E. Our project evaluated patient and clinician satisfaction on this. Method: We carried out a retrospective telephone questionnaire with patients over a one-week period during the pandemic. We focussed on overall satisfaction of the consultation and quality of communication. Consultants were also surveyed for their opinion on the clinics. Results: From 30 patients, 77% said they were 'very satisfied' with the overall experience. 80% of patients were 'very satisfied' with the overall length of the telephone consultation. 50% of patients felt the clinician was only 'adequately' able to assess them over the telephone. The consultants were less satisfied with the overall experience of telephone consultation. A common theme was that they felt ED documentation could be improved to help inform ongoing management. Conclusions: Overall, patients were satisfied with the consultations. It has been successful in minimising face to face consultations however some presentations necessitate further evaluation. We need to identify those injuries appropriate for virtual follow up and design a local protocol for these.